Helicobacter pylori: cellular immunity and protection from Multiple Sclerosis - Jenkins, Harry H. (2022)
Helicobacter pylori colonises the stomachs of almost half the world’s population, subverting host immunity to usually establish a life-long infection. Although asymptomatic in most cases, peptic ulcer disease and gastric cancer develop in a minority of those colonised. Recently, more evidence is emerging that the reducing prevalence of infections in developed countries is linked with the stark rise of allergy, asthma, and autoimmune diseases such as multiple sclerosis (MS).